2003
DOI: 10.1002/jcb.10668
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of PPARγ via active ERK1/2 leads to its physical association with p65 and inhibition of NF‐κβ

Abstract: Peroxisome proliferator-activated receptors (PPAR) are novel nuclear receptors and PPARgamma ligands have been shown to produce pro-apoptotic effects in many cancer cell types, including colon cancer. PPARgamma ligands exert their effect through PPARgamma-dependent (genomic) and PPARgamma-independent (non-genomic) mechanisms. Recent evidence suggests that PPARgamma ligands exert their pro-apoptotic effects in part by directly antagonizing the NF-kappabeta pathway as well as through activation of the MAP kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 38 publications
3
86
1
5
Order By: Relevance
“…This cell reporter system enabled us to examine this phenomenon without interfering undesired cellular components. Previous studies have indicated suppressive property of PPARc on NF-jB in various tissues (Sasaki et al 2005;Chen et al 2003;Remels et al 2009). One suggestive mechanism is inhibition of the IrB kinases (Sasaki et al 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This cell reporter system enabled us to examine this phenomenon without interfering undesired cellular components. Previous studies have indicated suppressive property of PPARc on NF-jB in various tissues (Sasaki et al 2005;Chen et al 2003;Remels et al 2009). One suggestive mechanism is inhibition of the IrB kinases (Sasaki et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…One suggestive mechanism is inhibition of the IrB kinases (Sasaki et al 2005). An alternative mechanism is phosphorylation of PPARc which physically interacts with p65 and subsequently decreases the transcriptional activity of NF-jB (Chen et al 2003). Therefore, further experiments are required to define which mechanism mediates ameliorative effects of PPARc on inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…75,76 ERK-mediated PPARg phosphorylation is observed in response to ciglitazone, epidermal growth factor (EGF), and platelet-derived growth factor (PDGF). 40 The effect of this phosphorylation is twofold. First, it inhibits PPARg/RXR binding to DNA, and second, it increases the association of PPARg with NF-kB.…”
Section: Posttranslational Regulation Of Ppar Activitymentioning
confidence: 99%
“…7,39 These gene-independent effects are mediated by direct binding of PPARs to transcription factors, including activator protein-1 (AP-1), pregnancyspecific-beta-1-glycoprotein (SP-1), nuclear factor-kappaB (NF-kB), and signal transducers and activators of transcription-1 (STAT-1). 6,7,25,[40][41][42][43] Binding to these transcription factors, in turn, prevents their activation and binding to DNA promoter elements. Additionally, PPARs can inhibit transcriptional activity by binding to and sequestering proteins that act as coactivators of these transcription factors (e.g., CREB, a coactivator of AP-1).…”
Section: Gene-dependent and -Independent Mechanisms Of Ppar Actionmentioning
confidence: 99%
See 1 more Smart Citation